Approach to the Study of NationalCultural Characteristics of Gender Stereotypes in the English and Uzbek Phraseological Units (Eurasian Journal of Humanities and Social Sciences, 2022)
The article contains information about the approaches that reveal the national and cultural identity of phraseological units, and the features of the functioning of the national mentality as linguistic thinking. The study of gender stereotypes in the linguistic landscape of these languages on the basis of the material of English and Uzbek phraseology is illustrated in the article. By means of a comparative analysis of English and Uzbek gender-marked phraseological units, similarities and differences in the formation of male and female characters in these languages are determined. These differences are explained by the national-cultural characteristics of the English and Uzbek languages and the historical conditions of their development. The theoretical side of the article is confirmed by a number of English and Uzbek gender-marked phraseological units